EMPLOYEE IDENTIFICATION AND PARTICIPATION IN THE VISION AND MISSION OF IT COMPANIES IN CHENNAI - Palani, A.; Kumarasamy, P. (International Journal of Psychosocial Rehabilitation, 2020)
It is undeniably, that organisations need to envision the future shape of the business in the form of having an integrated vision with a clear purpose exhibiting the essence of its corporate values. Mission statements on the other hand spells out the beliefs of the top management keeping in mind the future in clear cut terms. The objectives of this study are to study the level to which employees are able to identify the vision and mission statements of IT companies and to know how far the employees are able to participate in the vision and mission statements as being a part of the organisation. Most of the respondents agree that the vision and mission statement remind and motivates to work towards the organizational vision and mission statement, they remain committed also participate in pursuing the vision and mission statement.